047 An unusual cause of psychosis. Issue 12 (14th November 2019) - Mohamed, Ahmed Mubarak; Blackburn, Daniel; Iqbal, Ahmed; Prasad, Suveera
Abstract : A 24 year old woman was referred with a 3/52 history of headaches, memory problems, paranoia and confabulation. Examination was normal. AMT was 8/10. CT head and CSF were unremarkable. She self-discharged before an MRI. She was felt to have capacity. Four weeks later the psychiatry team sought advice reporting worsening symptoms. This patient was held under section. She reported significant headache, an unusual feature of a primary mental health problem. Anti NMDA of the serum and CSF were arranged (negative) an EEG did not show any concerning findings. During the hospital stay she managed to sneak off twice and was bought back by the police as it was felt that she lacked capacity. MRI revealed a pituitary microadenoma. She was assessed by Endocrinology. Extensive investigations concluded a diagnosis of 'Cushing disease'. Metyrpaone was administered for Cortisol suppression. Tansphenoidal surgery took place after. On subsequent clinic visits, gradual improvement in the symptoms was reported until ultimately she was completely back to her normal self (around 2/12 post-surgery). Discussion: Psychosis is a rare feature of Cushing disease. 1 This case demonstrates the diagnostic difficulties in these cases and the need of involvement and collaboration of different specialties for diagnosis and management. References: McCallum RW, Parameswaran V, Duffield A, Hoffman L, Burgess JR, Greenaway T. Cushing's disease presenting as a Schizophreniform psychosis. Endocrine Abstracts (2006):11;P117.